Robots and Workers: Evidence from the Netherlands - Daron Acemoglu; Hans R.A. Koster; Ceren Ozgen (Institute of Labor Economics (IZA), 2023)
We estimate the effects of robot adoption on firm-level and worker-level outcomes in the Netherlands using a large employer-employee panel dataset spanning 2009-2020. Our firm-level results confirm previous findings, with positive effects on value added and hours worked for robot-adopting firms and negative outcomes on competitors in the same industry. Our worker-level results show that directly-affected workers (e.g., bluecollar workers performing routine or replaceable tasks) face lower earnings and employment rates, while other workers indirectly gain from robot adoption. We also find that the negative effects from competitors' robot adoption load on directly-affected workers, while other workers benefit from this industry-level robot adoption. Overall, our results highlight the uneven effects of automation on the workforce.
Keywords: D63; E22; E23; E24; J24; O33; 330; robots; workers; technology; productivity; the Netherlands